2003
DOI: 10.1117/1.1556765
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Mediterranean extinction code (MEDEX)

Abstract: Abstract. The performance of electro-optical systems can be substantially affected by aerosol particles that scatter and absorb electromagnetic radiation. The model that is most frequently used for the prediction of aerosols and their effect on extinction in the marine atmosphere is the US Navy Aerosol Model (NAM). However, NAM can be significantly less reliable in coastal areas than on the open ocean. Based on an extensive series of measurements conducted on the island of Inisheer (Irish West Coast), an empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 44 publications
6
62
0
Order By: Relevance
“…The latter methods assume that the averaged particle concentration at a given wind speed represents the equilibrium distribution but is limited to the intermediate size range of particles (for more details, see Hoppel et al 2002). The aerosol size distributions used for the S3F calculations were measured on the island of Porquerolles for short fetch occurring during north-west wind conditions (Piazzola and Despiau 1997a;Piazzola et al 2003;Blot et al 2008). The results demonstrate the good performance of the flux formulation proposed by for particles in the 1-10 µm size range.…”
Section: Introductionmentioning
confidence: 83%
“…The latter methods assume that the averaged particle concentration at a given wind speed represents the equilibrium distribution but is limited to the intermediate size range of particles (for more details, see Hoppel et al 2002). The aerosol size distributions used for the S3F calculations were measured on the island of Porquerolles for short fetch occurring during north-west wind conditions (Piazzola and Despiau 1997a;Piazzola et al 2003;Blot et al 2008). The results demonstrate the good performance of the flux formulation proposed by for particles in the 1-10 µm size range.…”
Section: Introductionmentioning
confidence: 83%
“…However, since the release of the basic NAM, efforts have been reported that suggest the need to include more aerosol species 15 and to replace the AMP by fetch. 16,17 The fetch represents the distance an air mass has traveled over water, and thereby provides a first indication for the ratio of marine versus continental aerosols. The longer the air mass has spent over water, the more continental particles will have dispersed and deposited, and the more marine particles have been generated.…”
Section: Nam Overview and Initial Anam Developmentmentioning
confidence: 99%
“…Consequently, there have been requests to replace the AMP by a more accessible parameter. Piazzola et al developed the Mediterranean extinction code (MEDEX), 9 in which the AMP is replaced by fetch. The rationale for this is that the contribution of aerosols generated over land decreases in the absence of sources and due to gravitational settling as the air mass advects out over the sea.…”
Section: Introductionmentioning
confidence: 99%